(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper discusses the rationale for practically marking tone in the writing of Kĭkamba. It shows the limitations that readers of Kĭkamba encounter because of the absence of tone marking in its current orthography. Further, it describes the different tones present in the language and goes on to explain the functional load that tone carries in this language. Finally, it points out two different methods of marking tone and proposes one of them as the option that would adequately represent the tone of Kĭkamba without cluttering the text.